Response of the beginning of the partial root-zone drying irrigation in the performance of the sweet potato culture (Ipomoea batatas) - Sánchez D, Miguel A. (2020)
The objective of this study was evaluate, the response of the beginning of the Partial Root-Zone Drying Irrigation (PRD) in the performance of the sweet potato culture, for both the Huambachero and Paramonguino varieties. For this investigation drip irrigation was applied in two ways; with 100% of irrigation sheet and PRD with 50% of irrigation sheet, with three different beginnings of PRD; at 23, 33 and 45 days after sowing, watered with a frequency of 2 days. The yields for the control treatment were 42,1 t.ha-1 and 39,2 t.ha-1 for both the Huambachero and Paramonguino varieties and for the early PRD of 23, 33 and 45 days of 37,4 t.ha-1 , 32,7 t.ha-1 and 35,1 t.ha-1 , in the Huambachero variety and 30,0 t.ha-1 , 31,4 t.ha-1 and 32,6 t.ha-1 in the Paramonguino variety.The water application for both varieties was: 5368,9 m3 .ha-1 in the control treatment, 3185,54m3 .ha-1 , 3429,47 m3 .ha-1 and 3713,26 m3 .ha-1- for the PRD of 23, 33 and 45 days. Water productivity in the Huambachero variety were: control treatment 7,85 kg.m-3 , and for the beginning of PRD of 23,33 and 45 days of 10,91 kg.m-3 ,9,52 kg.m-3 and 9,46 kg.m-3 respectively. In the Paramonguino variety they were: control treatment 7,30 kg.m-3 and for the early days of PRD of 23, 33 and 45 days of 9,42 kg.m-3 , 9,15 kg.m-3 and 8,78 kg.m-3 respectively.